2017
DOI: 10.1210/jc.2017-00348
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal Sodium/Glucose Cotransporter 1 Expression Under Fasting Conditions Is Associated With Postload Hyperglycemia

Abstract: Duodenal SGLT-1 expression is increased in individuals with 1-hour postload hyperglycemia or IGT, as well as in subjects with T2DM, and it positively correlates with early postload glucose excursion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 38 publications
3
42
0
3
Order By: Relevance
“…A second potential mechanism underlying this effect may be explained by the recent observation of increased SGLT1 expression in pre-diabetes, TD2M and obesity and its positive association with intestinal glucose absorption and glucose excursion. 40,41 In response to intestinal glucose, plasma GIP, glucagon, insulin and SGLT1 were all higher in patients with obesity, compared with lean controls, while GLP-1 was lower. 41 Significant improvements in a number of metabolic parameters were also seen in this study following 12-weeks of treatment, including reduced waist circumference, a reduction in postprandial glucose and insulin and an increase in postprandial glucagon.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A second potential mechanism underlying this effect may be explained by the recent observation of increased SGLT1 expression in pre-diabetes, TD2M and obesity and its positive association with intestinal glucose absorption and glucose excursion. 40,41 In response to intestinal glucose, plasma GIP, glucagon, insulin and SGLT1 were all higher in patients with obesity, compared with lean controls, while GLP-1 was lower. 41 Significant improvements in a number of metabolic parameters were also seen in this study following 12-weeks of treatment, including reduced waist circumference, a reduction in postprandial glucose and insulin and an increase in postprandial glucagon.…”
Section: Discussionmentioning
confidence: 97%
“…FDA analysis of clinical trial data revealed that a 12-week weight loss of >5% achieved with lorcaserin of phenterminetopiramate was predictive of meaningful weight loss at 12 months following treatment,38 suggesting that the weight loss seen with licogliflozin by 12 weeks is promising. A second potential mechanism underlying this effect may be explained by the recent observation of increased SGLT1 expression in pre-diabetes, TD2M and obesity and its positive association with intestinal glucose absorption and glucose excursion 40,41. A significant increase in body weight was seen in both groups between the last treatment day and the end-of-study visit (+0.66 kg [80% CI, 1.96, 2.6] with placebo; P < 0.01 and + 2.3 kg [80% CI, 0.34, 0.98] with licogliflozin; P < 0.0001), suggesting that the weight-loss effects disappeared upon discontinuing treatment.…”
mentioning
confidence: 99%
“…Along with insulin sensitivity, secretion and clearance, a greater 1hPG during the OGTT may be explained by a more rapid appearance of oral glucose in the systemic circulation. 25,[45][46][47] As the rates of gastric emptying and intestinal glucose absorption were not measured, we could not evaluate the impact of oral glucose appearance on 1hPG levels.…”
Section: Discussionmentioning
confidence: 99%
“…NGT individuals with a glucose concentration at 1-hour glucose ≥8.6 mmol/L were found to have impaired beta-cell function and postprandial glucose absorption was not increased. Fiorentino et al compared duodenal SGLT-1 (sodium/glucose co-transporter 1) expression from biopsy specimens in individuals with NGT and 1-hour glucose <8.6 mmol/L, with those having NGT and 1-hour glucose ≥8.6 mmol/L 31. In contrast to the findings of Adams et al , the NGT 1-hour high group showed an increase in the expression of duodenal SGLT-1 explaining the increased 1-hour absorption of glucose.…”
Section: Discussionmentioning
confidence: 99%